Impact of administration route and gene polymorphisms on the serum concentration of voriconazole among Chinese patients with hematologic malignancies - Chen, Zhiyao; Zhang, Menghua; Wang, Lin; Cheng, Yuzhu; Miao, Liyan (Frontiers in Pharmacology, 2025)
AimsVoriconazole (VRC) is recommended as the first-line treatment for invasive fungal diseases (IFDs). Therapeutic drug monitoring (TDM)-based dose adjustments can be performed to implement the individualized use of VRC in clinical practice. Numerous studies have shown significant interindividual differences in serum VRC concentrations. It is important to identify risk factors for variations in VRC concentrations to develop TDM-based individualized VRC therapy. However, few studies have examined the impact of drug administration routes on VRC concentrations or the impact of gene polymorphisms on VRC concentrations under different administration routes in Chinese patients. This study aimed to investigate the effects of different administration routes and gene polymorphisms of CYP2C19, CYP3A4 and ABCB1 on serum VRC concentrations among Chinese patients with invasive aspergillosis.MethodsPatients (n = 160) who were administered VRC for the prophylaxis/treatment of IFDs were enrolled in this study. Quantitative analysis of VRC was performed via high-performance liquid chromatography coupled with tandem mass spectrometry. Nine types of single-nucleotide polymorphisms (SNPs) within CYP2C19, CYP3A4 and ABCB1 were detected via multiplex PCR and next-generation sequencing.ResultsThe Cmin of intravenous VRC was greater than the Cmin of oral VRC (2.3 vs. 1.5 μg/mL, respectively, P = 0.0006). The Cmin of serum VRC appears to be greater in those taking VRC by Q12h than in those taking Bid and Qd when administered orally (3.8 vs. 1.4 μg/mL, respectively, P = 0.0045; 3.8 vs. 0.8 μg/mL, P = 0.0173). Within the IV + Oral and Oral groups of CYP2C19, the Cmin of the serum VRC in the NMs was significantly lower than that in the IMs (1.42 vs. 2.21, P = 0.0108; 1.03 vs. 1.89, P = 0.0386). Within the IV group of CYP3A4 rs4646437, the Cmin of the serum VRC in the GGs was significantly greater than that in the GA + AA group (2.41 vs. 1.43, respectively, P = 0.0402). Similarly, in both the IV + Oral and IV groups of CYP3A4 rs2242480, the Cmin of serum VRC in the CCs was markedly greater than that in the (CT + TT)s (2.18 vs. 1.47, respectively, P = 0.0292; 2.47 vs. 1.45, respectively, P = 0.0173). Moreover, among the oral groups of patients with ABCB1 rs1128503, patients with the wild-type genotype presented significantly greater serum VRC Cmin than those with the mutant genotype (1.89 vs. 1.13, respectively, P = 0.0477).ConclusionThe Cmin of intravenous VRC was greater than the Cmin of oral VRC when patients were treated with the recommended dosage. Oral administration of VRC via Q12h is optimal for obtaining a higher Cmin of serum VRC. Furthermore, attention should be given to VRC serum concentrations in patients with mutations in CYP2C19. The CYP3A4 rs2242480 and CYP3A4 rs4646437 genotypes may primarily affect VRC concentrations during intravenous administration, whereas ABCB1 rs1128503 primarily affects VRC concentrations during oral administration.